A generalized stochastic production frontier analysis of technical efficiency of rice farming: A case study from Assam, India. Issue 2 (14th November 2016) - Bhattacharyya, Aditi; Mandal, Raju
Abstract : Purpose: This paper aims to analyze farm-level technical inefficiency of rice farming in Assam, India, using a multiple-output generalized stochastic frontier framework. Design/methodology/approach: Primary data for this study were collected in 2009-2010 from 310 farm-households in four non-contiguous districts of Dhubri, Morigaon, Dibrugarh and Cachar that are located in different agro-climatic regions of Assam. Based on a Cobb–Douglas production function for multiple rice varieties, the paper simultaneously estimates the generalized stochastic production frontier and examines effects of exogenous factors on farm-level technical inefficiency. Findings: Results of this study show that the average technical inefficiency of farms is 8.5 per cent in the sample. Further, inefficiency is lower in the frequently flood prone areas, and availability of government support helps reduce such inefficiency as well. However, technical efficiency is higher for the Muslim farm-households, and it decreases with greater land fragmentation. The study also finds that the use of primitive technology like bullock reduces technical efficiency of rice farming. Originality/value: This paper is based on a novel data set that has specially been collected to examine productivity and efficiency of rice cultivation in the flood plains of Assam that has not been studied before. Further, to the best of the authors' knowledge, this paper is the first one to model rice production as a multiple-output stochastic production frontier and analyze technical efficiency of rice production accordingly.